IMPACT OF NURSE STAFFING RATIOS ON PATIENT MORTALITY RATES - Ahmed Abdullah Albudukhi , Hussain Jassem Alnasser , Hejji Hasan Alatiya , Yahya Hussain Al Haddaf , Abdullatif Fahad Alsaliemy , Mohammed Abdul Mohsen Alaqnam , ,; Bader Khalil Al Jaber , Ahmed Mohammad Albader , Zainab Salman Alhamood , Ibrahim Mohammed Alali , Ali Yousef Al Qadhi , Ghassan Yassin Albaghli , Safa Mohammed Ban Ashwan ,Dafi Yousef Al-Sarhan,Mazen Mhsn Ali Alharbi, (Chelonian Research Foundation, 2022)
The research does not consistently show statistically significant inverse correlations between levels of nurse staffing and hospital mortality. The link can be effectively addressed in critical care settings owing to the presence of patients with severe medical conditions and high death rates, the need for intensive nursing care, and the availability of specific tools to compensate for individual risk factors. This research presents a literature analysis examining the relationship between staffing levels of critical care nurses and patient mortality. A comprehensive search was conducted on major electronic databases, such as MEDLINE, EMBASE, and the Cumulative Index of Nursing and Allied Health Literature. The search phrases included critical/intensive care, health care quality, hospital mortality, personnel staffing and scheduling, and hospital nursing staff. The examined studies did not provide any clear evidence of the influence of nurse staffing levels on patients' hospital mortality in critical care settings. Methodological obstacles that may have hindered accurate evaluation of the relationship include difficulties in measuring exposure status and the presence of uncontrolled confounding variables. The absence of correlation also suggests that hospital mortality may not be sufficiently responsive to identify the impacts of inadequate nurse staffing levels in critical care environments. Keywords: mortality rate, nurse, review, hospital nursing staff, patient.